Republic of Congo : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility-Staff Report; Staff Supplements; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
With the Heavily Indebted Poor Countries (HIPC) completion, Congo's prospects for achieving sustained growth and poverty reduction have improved. The HIPC completion reduced debt service obligations and increased the resilience of external debt indicators to shocks. Non-oil revenue is improved through broadening the tax base and improving the design of the tax system. The objectives of the poverty reduction strategy (PRS) and fiscal sustainability would require lasting gains in non-oil revenue collection. IMF staff welcomes the authority's good faith efforts to obtain comparable treatment from all remaining commercial creditors.